2014
DOI: 10.1371/journal.pone.0108104
|View full text |Cite
|
Sign up to set email alerts
|

Similar Source of Differential Blood mRNAs in Lung Cancer and Pulmonary Inflammatory Diseases: Calls for Improved Strategy for Identifying Cancer-Specific Biomarkers

Abstract: BackgroundMany studies try to identify cancer diagnostic biomarkers by comparing peripheral whole blood (PWB) of cancer samples and healthy controls, explicitly or implicitly assuming that such biomarkers are potential candidate biomarkers for distinguishing cancer from nonmalignant inflammation-associated diseases.MethodsMultiple PWB gene expression profiles for lung cancer/inflammation-associated pulmonary diseases were used for differential mRNAs identification and comparison and for proportion estimation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Hong et al suggested that the selection of candidate blood-based mRNA biomarkers for distinguishing cancer from inflammation-associated diseases may yield misleading results, [19] meaning that many serologic tumor markers were affected by inflammation in peripheral blood. Our study further explored the diagnostic capacity of AFP to WBC ratio, which was the worst for the prediction of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al suggested that the selection of candidate blood-based mRNA biomarkers for distinguishing cancer from inflammation-associated diseases may yield misleading results, [19] meaning that many serologic tumor markers were affected by inflammation in peripheral blood. Our study further explored the diagnostic capacity of AFP to WBC ratio, which was the worst for the prediction of HCC.…”
Section: Discussionmentioning
confidence: 99%